A relação família-escola e a infância em tempos de pandemia - Rocha, Priscila Kely da (2022)
The removal of schools, caused by the Covid-19 pandemic, has led children to study at home; showed, in many cases, how far the families were from the institution and from their children's learning. At that moment, family relationships were put in check. There were several challenges faced by the family and the child away from the conviviality of relatives, friends, school, teachers; away from spaces where she could express herself, play, experiment and experience new experiences. Remote teaching has become the only option so that the rights to learn school content are not suppressed at the most critical moment of the pandemic; consequently, family relationships were positively and/or negatively affected. Knowing the consequences suffered by all humanity at this time of impacts on health, economy, loss of loved ones, professional and school activities being developed in other ways, including social isolation, our hypothesis was that the relationships between children, family and school were significantly affected. The relationship between family and school needed to be strengthened. Family members and children were faced with an almost full-time coexistence, which brought contradictions in the relationships that permeated different results, ranging from affective approximation, greater acceptance and participation in learning to the neglect of school dropout and vulnerability, with abuse and violence. The pandemic also showed that the child remains the most fragile link in relationships. Whether in the family, at school or in their community, there is little space for listening and welcoming their demands and feelings. in their community, there is little space for listening and welcoming their demands and feelings. It was presented as a problem of the present research to understand the way in which family relationships were affected by the pandemic, as well as the relationship between the family, school and children in early childhood education during the period of confinement and remote school. The object of this research was family relationships and the way they were affected by the pandemic. We sought to answer the following question: were the relationships between family, school and childhood affected with remote teaching in times of pandemic and quarantine? As an objective, the research proposed to understand how and if the confinement imposed by the pandemic affected family relationships. It established as specific objectives: to understand how children and family perceive their relationship and map how this category presented itself in everyday relationships during the pandemic. The research universe was a municipal public school, located in the city of Guarulhos, and the subjects were five families and children from Early Childhood Education enrolled in that school. The methodology used was of a qualitative nature, and the data collection instruments were semi-structured interviews with families and children. There were also home visits for data collection and classroom activities with the children for the same purpose. As they are small children, in addition to the semi-structured interview, it was proposed to the children, subjects of this research, to express their perceptions of the relationship with their family and with the school through drawings.